The Effect of Realistic Mathematics Education (RME) on Mathematical Reasoning Ability and Critical Thinking of Elementary School Students in Plane Figures Material - Rasyidah Rasyidah; Maisura Maisura; Syifa Saputra; Yulia Santi; Ety Mukhlesi Yeni (FKIP - Universitas Riau, 2026)
This study investigated the effect of Realistic Mathematics Education (RME) on mathematical reasoning and critical thinking abilities of second-grade elementary students in plane figures material. The low performance in base on initial observations and preliminary observations showing only 27.27% of students solving contextual problems successfully motivated this research. A quasi-experimental design with one-group pretest-posttest involving 30 second-grade students at UPTD SD Negeri 12 Makmur was employed. Data were collected using validated written tests measuring mathematical reasoning and critical thinking abilities. The Shapiro-Wilk test confirmed normal data distribution, and paired sample t-test analyzed the intervention effects. Results showed significant improvements in both abilities. Mathematical reasoning increased from a mean of 59.33 to 79.67 (gain = 20.34, t = -30.113, p < 0.001), while critical thinking improved from 57.00 to 73.83 (gain = 16.83, t = -16.793, p < 0.001). These findings demonstrate that RME significantly enhances students' mathematical reasoning and critical thinking by engaging them in contextual problem-solving, guided reinvention, collaborative discussions, and progressive mathematization from concrete to abstract thinking. The study provides empirical evidence supporting RME implementation in elementary mathematics education to develop higher-order thinking skills through meaningful, real-world learning experiences.